THERMAL ANALISYS FOR A BILATERAL LINEAR INDUCTION MOTOR WITH SECTIONED PLATE ARMATURE - Chiriac, Gabriel (European Scientific Journal, ESJ, 2013)
The paper presents an analysis of the thermal regime for a double sided linear induction motor with ring windings and sectioned plate armature which is sectioned with vertical cutting-up. The sectioned armature is done in order to reduce the eddy currents into the plate, which are not useful for the traction force of the linear motor. The motor can operate in an oscillating drive system with fast response and low distance movement or for small and medium movement application. For different forces developed by the motor, a thermal modeling is realized for the linear induction motor and it is compared with experimental data regarding the thermal aspects. The theoretical characteristics of the motor heating overlap the experimental characteristics and confirm the validity of the thermal model.